Translational reprogramming marks adaptation to asparagine restriction in cancer - Pathria, Gaurav; Lee, Joo Sang; Hasnis, Erez; Tandoc, Kristofferson; Scott, David A.; Verma, Sachin; Feng, Yongmei; Larue, Lionel; Sahu, Avinash D.; Topisirovic, Ivan; Ruppin, Eytan; Ronai, Ze’ev A. (Nature cell biology, 2019)
While amino acid restriction remains an attractive strategy for cancer therapy, metabolic adaptations limit its effectiveness. Here we demonstrate a role of translational reprogramming in the survival of asparagine-restricted cancer cells. Asparagine limitation in melanoma and pancreatic cancer cells activates receptor tyrosine kinase–MAPK signalling as part of a feedforward mechanism involving mammalian target of rapamycin complex 1 (mTORC1)-dependent increase in MAPK-interacting kinase 1 (MNK1) and eukaryotic translation initiation factor 4E (eIF4E), resulting in enhanced translation of activating transcription factor 4 ( ATF4 ) mRNA. MAPK inhibition attenuates translational induction of ATF4 and the expression of its target asparagine synthetase (ASNS), sensitizing melanoma and pancreatic tumours to asparagine restriction, reflected in inhibition of their growth. Correspondingly, low ASNS expression is among the top predictors of response to inhibitors of MAPK signalling in patients with melanoma and is associated with favourable prognosis when combined with low MAPK signalling activity. These studies reveal an axis of adaptation to asparagine deprivation and present a rationale for clinical evaluation of MAPK inhibitors in combination with asparagine restriction approaches. Translational reprogramming during asparagine restriction, via activated MAPK signalling and enhanced translation of activating transcription factor 4 ( ATF4 ) mRNA in melanoma and pancreatic cancer cells, provide a survival advantage.